PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA SEKOLAH DASAR KELAS V - Septian Mulyadi; Mohd. Fauziddin; Yanti Yandri Kusuma; Musnar Indra Daulay; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to improve the critical thinking skills of fifth-grade students at SDN 001 Langgini through the implementation of the Cooperative Learning Jigsaw model in Natural and Social Sciences (IPAS) during the odd semester of 2024. This study employed a Classroom Action Research (CAR) method with two cycles, each consisting of two meetings and including the stages of planning, implementation, observation, and reflection. The subjects were 14 students, consisting of 9 male and 5 female students. Data were collected using critical thinking tests, classroom observation of teacher and student activities, and documentation. The results indicated that the Jigsaw model effectively improved students’ critical thinking skills. In Cycle I, the classical completeness reached 43% with 6 students achieving the criteria, while in Cycle II it increased to 86% with 12 students completing the criteria. Observation data also showed an increase in students’ active involvement during the learning process. It can be concluded that the Cooperative Learning Jigsaw model is effective in enhancing the critical thinking skills of fifth-grade students at SDN 001 Langgini.